Taxonomic revision, phylogeny, and cyst wall composition of the dinoflagellate cyst genus Votadinium Reid (Dinophyceae, Peridiniales, Protoperidiniaceae). (2nd April 2020) - Gurdebeke, Pieter R.; Mertens, Kenneth N.; Pospelova, Vera; Matsuoka, Kazumi; Li, Zhen; Gribble, Kristin E.; Gu, Haifeng; Bogus, Kara; Vrielinck, Henk; Louwye, Stephen
Abstract: The taxonomy of the dinoflagellate cyst-based genus Votadinium has been in need of revision. This is accomplished here by integrating morphology, large subunit (LSU) rDNA sequences, and cyst wall composition analyses through micro-Fourier transform infrared spectroscopy. Three new species, Votadinium pontifossatum, V. rhomboideum and V. reidii, are described as cyst stages of Protoperidinium paraoblongum, P. quadrioblongum, and P. steidingerae, respectively. A previously undescribed type of ornamentation is reported for V. pontifossatum . A fourth new species is assigned to V. concavum . Furthermore, Lejeunecysta psilodora Benedek (= Lejeunecysta psuchra Matsuoka), is re-described as V. psilodora and the holotype re-illustrated, as is done for the holotype of V. spinosum Reid. New illustrations are provided for V. elongatum and V. nanhaiense . LSU rDNA sequences of V. concavum reveal its placement in the Oceanica section of the genus Protoperidinium, supporting earlier evidence that the Oceanica section and the cyst-based genus Votadinium form a monophyletic clade. Thus, Votadinium could be considered the cyst equivalent of the motile-defined Oceanica section. The cyst walls of Votadinium spinosum, V. calvum and V. pontifossatum are built from carbohydrate-based macromolecules with N-containing functional groups, in agreement with the heterotrophic nature of their motile stage. Comparison with related genera Trinovantedinium and Quinquecuspis reveals that the species and genera can be separated based on cyst wall composition, supporting a phylogeny based on molecular data and/or ecological differences. Furthermore, Trinovantedinium applanatum spectra unexpectedly show an additional absorption at 1510 cm −1, indicating an aromatic group that is commonly reported for sporopollenin and not seen in dinoflagellate cysts so far. This study stabilizes the taxonomy of the cyst genus Votadinium, clarifies its relationship to the Oceanica section of Protoperidinium, and further supports the application of whole cyst wall chemistry in helping address problems in dinoflagellate cyst taxonomy and ecology.